PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PERUMAHAAN CIUJUNG INDAH - Surti Zahra; Nugrahini Kusumawati; Mamay Komarudin; Wahyu Widodo; Nia Nuraeni (Gapenas Publisher, 2022)
Increased consumer purchasing decisions can be influanced by several factors such as price and quality of service,by providing affordable prices and while maintaining service quality, it will be able to improve purchasing decisions.This study aims to determine the effect of price and service quality on purchasing decisions in ciujung indah housing.The reaserch method used is kuantitatif with a population off 117 consumers and sampel of 91 respondents using the probability sampling method, the sampling technique is random sampling with calculations using the slovin formula for consumers in ciujung indah housing. researchers use it to get the results of validity, reliability, classical, assumptions, multiple regression and hypothesis testing. Based on hypothesis testing, it can be concluded that price affects purchasing decisions and service quality affects purchasing decisions and simultan eously price and service quality affect purchasing decisions